The Use of Yura Yunita's Song Tutur Batin Media in Learning Poetry Writing Skills - Bathari Sekarwangi Eka Putri; Sahlan Mujtaba; Imam Muhtarom (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
The purpose of this study was to determine the effect of using Yura Yunita Tutur Batin song media in improving poetry writing skills in class X students. This study used a quantitative approach using experimental research methods. The experimental design used in this study was quasi-experimental using a nonequivalent control group design. The research sample used in this study consisted of 35 students from class X at SMA Negeri 17 Bekasi, who were assigned to the experimental class (X E.2), and 33 students from the same class who were assigned to the control class (X E.5). Data on poetry writing skills were collected using test instruments that were compiled objectively based on test specifications. In its implementation, the experimental class received treatment to use song media in poetry learning, while the control class did not receive song media treatment. However, both classes were given the same learning materials and resources. The research data were analyzed using parametric inferential statistical procedures, namely paired sample t-tests. The results of this study: 1) the pre-test of poetry writing skills, namely before using song media in learning, had an average value of 67.37 for the experimental class and 69.36 for the control class; 2) post-test of poetry writing skills, namely without using song media in learning, had an average value of 82.27 for the control class, while for the experimental class that used song media in learning, had an average value of 87.11; 3) song media had a significant influence in improving poetry writing skills in class X of SMA Negeri 17 Bekasi.